Indonesian migrant workers in Hong Kong: Smartphone culture and activism - Irfan Wahyudi; Panizza Allmark (Faculty of Social and Political Science, Universitas Airlangga, 2020)
This article focuses on contemporary smartphone culture and activism performed by female Indonesian migrant domestic workers in Hong Kong. There are around 330.000 migrant workers in Hong Kong, and wherein 150.000 originated from Indonesia. Most of the Indonesian migrant workers in Hong Kong work in the domestic sectors: housemaid, babysitter, and career. They are obliged to live with their employer and start working from five mornings until late at night for six days a week. The smartphone is their primary medium in keeping a connection with friends and families back home and reduces social isolation. Interestingly, Indonesian migrant workers also use smartphones for activism to support migrant workers’ rights issues. Despite the isolation issues and the social limitations experienced by the Indonesian migrant workers’, this article aims to explore the following questions: how is smartphone culture developed in Indonesian migrant workers’ communication activities in Hong Kong? How is the smartphone, in particular, used as the medium for activism? Using the netnography method, this research explores the smartphone culture and activism performed by Indonesian migrant workers’ in their online routine. Smartphone usage has become an interesting phenomenon where this device has changed the cultural habits and further forms a new cultural pattern. Social media platforms and chat applications on smartphones have facilitated Indonesian migrant workers’ more comprehensive access to information. It is found that social media access is essential for Indonesian migrant workers to ease loneliness and further used as their medium of existence in the virtual world. Furthermore, they also create virtual identities through social media, share experiences and views through online platforms, and organize protests or other forms of activism. Sulistyaningsih’s case is a clear example of how communication access was crucial for Indonesian migrant workers at a time of danger. The diverse forms of communication technology have allowed them to create compelling messages. This activity provides evidence that Indonesian migrant workers still can be creative despite their long working hours.